Common and gender‐specific associations with cocaine use on gray matter volume: Data from the ENIGMA addiction working group. Issue 1 (28th August 2020) - Rabin, Rachel A.; Mackey, Scott; Parvaz, Muhammad A.; Cousijn, Janna; Li, Chiang‐shan; Pearlson, Godfrey; Schmaal, Lianne; Sinha, Rajita; Stein, Elliot; Veltman, Dick; Thompson, Paul M.; Conrod, Patricia; et al.
Abstract: Gray matter volume (GMV) in frontal cortical and limbic regions is susceptible to cocaine‐associated reductions in cocaine‐dependent individuals (CD) and is negatively associated with duration of cocaine use. Gender differences in CD individuals have been reported clinically and in the context of neural responses to cue‐induced craving and stress reactivity. The variability of GMV in select brain areas between men and women (e.g., limbic regions) underscores the importance of exploring interaction effects between gender and cocaine dependence on brain structure. Therefore, voxel‐based morphometry data derived from the ENIGMA Addiction Consortium were used to investigate potential gender differences in GMV in CD individuals compared to matched controls (CTL). T1‐weighted MRI scans and clinical data were pooled from seven sites yielding 420 gender‐ and age‐matched participants: CD men (CDM, n = 140); CD women (CDW, n = 70); control men (CTLM, n = 140); and control women (CTLW, n = 70). Differences in GMV were assessed using a 2 × 2 ANCOVA, and voxelwise whole‐brain linear regressions were conducted to explore relationships between GMV and duration of cocaine use. All analyses were corrected for age, total intracranial volume, and site. Diagnostic differences were predominantly found in frontal regions (CD < CTL). Interestingly, gender × diagnosis interactions in the left anterior insula and left lingual gyrus were also documented, driven by differences in women (CDW < CTLW). Further, lower right hippocampal GMV was associated with greater cocaine duration in CDM. Given the importance of the anterior insula to interoception and the hippocampus to learning contextual associations, results may point to gender‐specific mechanisms in cocaine addiction. Abstract : Given the variability of gray matter volume (GMV) in select brain areas between men and women, we used voxel‐based morphometry data derived from the ENIGMA Addiction Consortium to investigate potential gender differences in GMV in cocaine‐dependent (CD) individuals compared to matched controls (CTL). Interestingly, gender × diagnosis interactions in the left anterior insula and left lingual gyrus were documented, driven by differences in women (CD < CTL). Further, lower right hippocampal GMV was associated with greater cocaine duration in only CD men.